Migration for ecological preservation? Tibetan herders' decision making process in the eco-migration policy of Golok Tibetan autonomous prefecture (Qinghai province, PRC). (1st January 2015) - Bessho, Yusuke
Abstract : This paper considers nomads' decision-making process in response to the 'Eco-Migration Policy' in the Three River Headwaters region of the People's Republic of China. Contrary to previous studies of this policy, which emphasised the need for pastoral communities to wholly assimilate to urban life, this study focuses on individual choices and on the practical meanings of pastoralists' decisions in relation to government policies. Interviews and field surveys revealed the main factors inducing Tibetan pastoralists to become ecological migrants: whether the migrant village was in a convenient location and the facilities were satisfactory, the retention of the right to profit from caterpillar fungus collection, and the flexibility of livestock leases. These rationales stand in stark contrast to the notion of 'environmental correctness' emphasised in the state's discourse regarding these policies.